UNDERSTANDING THE NUANCES OF MODAL VERBS IN EXPRESSING PERMISSIONS, OPPORTUNITIES, AND RESPONSIBILITIES - Tolibova Durdona Mamajonovna (Scientific Impulse, 2024)
In this article, modal verbs are effectively highlighted their diverse roles in expressing permissions, opportunities, and responsibilities. The structured breakdown of modal verbs by categories, such as permissions, opportunities, and responsibilities, provides a clear understanding of how these verbs operate within different contexts. The examples provided illustrate nuanced usage of each modal verb, offering practical insights into their functions in every day communication